2016
DOI: 10.1007/s10753-016-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Inhibits NLRP3 Inflammasome and Attenuates Blast-Induced Traumatic Brain Injury in Rats

Abstract: Increasing evidence has demonstrated that inflammatory response plays a crucial role in the pathogenesis of secondary injury following blast-induced traumatic brain injury (bTBI). Propofol, a lipid-soluble intravenous anesthetic, has been shown to possess therapeutic benefit during neuroinflammation on various brain injury models. Recent findings have proved that the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome involved in the process of the inflammatory response following brain tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 37 publications
3
66
0
Order By: Relevance
“…Similarly, another paper studying the effect of propofol in rats subjected to blast TBI demonstrated a reduced NLRP3 activation and a consequent ameliorated brain damage due to the antioxidant and ROS scavenger effect of propofol (Ma et al, 2016). This NLRP3 blocking strategy is again rather indirect than direct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another paper studying the effect of propofol in rats subjected to blast TBI demonstrated a reduced NLRP3 activation and a consequent ameliorated brain damage due to the antioxidant and ROS scavenger effect of propofol (Ma et al, 2016). This NLRP3 blocking strategy is again rather indirect than direct.…”
Section: Discussionmentioning
confidence: 99%
“…The few papers, so far published on the role of NLRP3 in TBI used indirect strategies to prevent NLRP3 activation (Liu et al, 2013; Dong et al, 2016; Ma et al, 2016; Wei et al, 2016; Lin et al, 2017). A study using telmisartan in mice subjected to cold brain injury showed that the treatment reduced oxidative stress and brain oedema, as a consequence NLRP3 and IL-1b production were decreased; however, the effect on this pathway is rather indirect than direct (Wei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond neurodegenerative diseases, inflammasome forming NLRs have also been found to significantly modulate various pathologic features of both traumatic and non-traumatic brain injury. Of the inflammasome forming NLRs in brain injury, the NLRP1 and NLRP3 inflammasomes are the best characterized in mice and the majority of studies have focused on mechanisms associated with regulating IL-1β/IL-18 and pyroptosis (68, 45, 50). However, aside from the inflammasome, there is a paucity of data pertaining to the role of non-inflammasome forming regulatory NLRs in brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several inflammasome forming NLRs have been evaluated in the context of brain injury. For example, multiple studies have suggested that NLRP1 and NLRP3 may play critical regulatory roles in TBI in both humans and rodents (68). Moreover, NLRC4 and AIM2 have also been implicated in contributing to non-traumatic brain injury in stroke models (9).…”
Section: Introductionmentioning
confidence: 99%
“…Protein levels of NLRP3, active caspase-1, and IL-18 all gradually increased over the course of 7 days in cortical tissue ipsilateral to the contusion, while levels of IL-1β rose at 6 h post-injury and declined over the course of 7 days to sham levels [54]. In support of the role of NLRP3 in TBI, another animal study showed that the expression of NLRP3, caspase-1, and thioredoxin-interacting protein (TXNIP), a regulator of NLRP3 activity, were all increased in the cerebral cortex of rats at 12 and 24 h post-blast injury [55]. In a luidpercussion model of TBI in rats, NLRP1 inlammasome complexes containing ASC, caspase-1, caspase-11, XIAP, and pannexin-1 with resultant caspase-1 activation and XIAP cleavage were present in injured cortical lysate at 4 h post-injury.…”
Section: The Inlammasome and Pro-inlammatory Cytokine Releasementioning
confidence: 93%